Reliable real-time output gap estimates based on a modified Hamilton filter - Josefine Quast; Maik H. Wolters (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2019)
The authors contribute to the debate regarding the reliability of output gap estimates. As an alternative to the Hodrick-Prescott (HP) filter, they propose a simple modification of the filter proposed by Hamilton in 2018 that shares its favorable real-time properties, but leads to a more even coverage of typical business cycle frequencies. Based on output growth and inflation forecasts and a comparison to revised output gap estimates from policy institutions, they find that real-time output gaps based on the modified Hamilton filter are economically much more meaningful measures of the business cycle than those based on other simple statistical trend-cycle decomposition techniques such as the HP or the Bandpass filter.
urn:nbn:de:hebis:30:3-500573
Keywords: C18; E32; E37; 330; output gap; potential output; trend-cycle decomposition; Hamilton filter; real-time data; inflation forecasting